μ-Oxo-Bridged Hypervalent Iodine(III) Compound as an Extreme Oxidant for Aqueous Oxidations - Dohi, Toshifumi; Nakae, Tomofumi; Takenaga, Naoko; Uchiyama, Teruyoshi; Fukushima, Kei-ichiro; Fujioka, Hiromichi; Kita, Yasuyuki (Synthesis, 2012)
We have found that in aqueous oxidations the μ-oxo-bridged hypervalent iodine trifluoroacetate reagent 1 {[(PhI(OCOCF3)]2O} is generally more reactive than the corresponding monomeric reagent, especially toward phenolic substrates. μ-Oxo-bridged 1 in aqueous media thus provided dearomatized quinones 3 in excellent yields in most cases compared to conventional phenyliodine(III) diacetate and bis(trifluoroacetate), as a result of the rapid oxidation of both phenols and naphthols 2. Furthermore, the oxidation reactions proceeded even in water using water-soluble μ-oxo oxidant 1, which has promise for μ-oxo-bridged reagent 1 to become the favored reagent over hydrophobic phenyliodine(III) diacetate and bis(trifluoroacetate).
Keywords: hypervalent iodine; active reagent; quinones; oxidation; phenols